Youtubers mirins e a formação da identidade feminina: uma análise do canal Planeta das Gêmeas - Oliveira, Daiane de (2021)
The present research has as a problem the following question: How is it structured, what contents are presented in the discourse broadcast on the Planeta das Gêmeas channel and how do they act in the constitution of female identity? From this question, we list as general objective: To analyze the role of YouTube in the constitution of children's identities. In view of this general objective, we seek to pay attention to the structuring, content and discourse presented on the Planeta das Gêmeas channel and how they act in the (con)formation of children's subjectivities. Therefore, as specific objectives, we list: Reflect on the concept of childhood and child today and the relationship with contemporary media; To problematize the relationship between subjectivity and gender; To analyze the discourse and images broadcast by the Planeta das Gêmeas channel in order to identify possible implications for the constitution of female identity. Such research falls within the scope of cultural studies, and the videos here are understood within this conceptual category. Methodologically, from the problem and objectives listed, and considering the insertion of the investigation in the field of cultural studies, it is a qualitative and bibliographic research, with documental analysis, since it considers the videos of the Planeta das Gêmeas Channel as documents. Two videos were selected and as a criterion we considered the time of publication being an older one from 2017 and another more recent from 2021, in order to be able to make a comparison between the two documents. The videos were described in terms of their content, language used, scenario presented, products highlighted, among other points. By analyzing the discourse and images broadcast by the Planeta das Gêmeas channel, we identified recurrences of themes and strategies, such as early adultization, advertising disguised as content and others with possible implications for the constitution of female identity. With childish language, they resort to the presentation of apparatus, clothes and situations that are inappropriate for childhood, but strategically designed under the logic of advertising and consumption, aimed at children and disguised as content in the videos. We conclude that it is extremely important to consider these productions as permeated by power relations and constituents of subjectivities, as they influence behaviors and ways of being of children who watch the videos published on the Planeta das Gêmeas channel.